Manipulation of environmental stress towards lutein production in chlorella fusca cell culture - Othman, Rashidi; Mohd Hassan, Norazian; Abu Bakar, Ainaa Eliah; Noh, Nur Hidayah; Ahmad Fadzillah, Nurrulhidayah; Mahmad, Noraini (SET Publisher, 2019)
All carotenoids originate from a single, common precursor, phytoene. The colour of carotenoids is determined by desaturation, isomerization, cyclization, hydroxylation and epoxidation of the 40-carbon phytoene. The conjugated double-bond structure and nature of end ring groups confer on the carotenoids properties such as colour and antioxidant activity. Algae may become major sources of carotenoids but the extent of environmental stress and genetic influences on algae carotenoid biosynthesis are poorly understood. Carotenoid biosynthesis can be influenced by many aspects and is liable to geometric isomerization with the existence of oxygen, light and heat which affect the colour degradation and oxidation. Therefore, in this study carotenoid biogenesis is investigated in cell culture of Chlorella fusca as a potential model system for rapid initiation, and extraction of carotenoids by providing stringent control of genetic, developmental and environmental factors. The value of this experimental system for investigating key factors controlling the carotenoid accumulation is then tested by assessing the effects of environmental variables, such as drought stress, light intensity, nutrient strength and media formulation on carotenoid accumulation. Our findings revealed that the conversion of violaxanthin to lutein is due to irradiance stress condition, nutrient strength as well as drought stress. As a result, manipulation of environmental variables will up-regulate lutein concentration. This reaction will restrict the supply of precursors for ABA biosynthesis and the algae cell culture responds by increasing carotenogenic metabolic flux to compensate for this restriction. In conclusion, selecting the appropriate algae species for the appropriate environmental conditions is not only important for yield production, but also for nutritional value quality of carotenoid.